Teknologi Pengomposan Limbah Kulit Durian Menggunakan EM4 - Jumar Jumar; Riza Adrianoor Saputra; M. Shaleh Wafiuddin (EnviroScienteae, 2020)
Durian rind waste is a source of organic material that is easily found during the durian fruit season in South Kalimantan, where the potential abundance can reach 100 tons / day. If left unchecked, it will involve environmental problems such as garbage build-up, strong odors, and aesthetically disturbing views, so special care needs to be taken on the organic waste. Therefore, a solution is needed to overcome this problem by using durian rind waste as raw material for composting. The purpose of this study was to study how to apply the EM4 dose to the quality of durian skin waste compost. This study used a single complete randomized design (CRD) consisting of 6 preparations: s0 (0 mL EM4 / kg material), s1 (1 mL EM4 / kg material), s2 (1.5 mL EM4 / kg material), s3 (2 mL EM4 / kg material), s4 (2.5 mL EM4 / kg material), s5 (3 mL EM4 / kg material). The results showed that what was needed in the study with the help of 1 mL EM4 / kg material (S1), where the durian skin compost was in accordance with SNI on the pH parameters namely 7.48, C-organic 16.59%, total N 1.34%, moisture content 42.54%, temperature 30oC, and compost odor test with criteria not approved rotten.